#TITLE_ALTERNATIVE# - ARIZAL (NIM : 12213031), FREDDY
Abstract Microbial Enhanced Oil Recovery (MEOR) is an application that utilizes the ability of microorganism to increase oil recovery from oil reservoir. The indigenous bacteria produce some substances which affect the oil and reservoir. Laboratory research has demonstrated that microbial products can change the chemical and physical properties of oil and increase the oil recovery. In this study, the focus is about nutrients of biostimulation effect on artificial core (permeability 5-300 mD; porosity 0.2-0.35) to determine the tertiary oil recovery. The process of this stimulation is separated into 3 sessions which are making the artificial cores, waterflooding the oil-saturated core with formation water, and imbibition process with imbibition fluid. The nutrients formulation which can increase the growth of indigenous microorganism and change the oil characteristic from well X in South Sumatra will be used to determine the tertiary oil recovery. The result of optimum nutrients concentration based on statistical analysis of central composite design which has been done in the previous research i.e. molasses 7,16% (v/v), (NH4)2HPO4 1% (w/v) and urea 1% (w/v). It will be mixed with formation water sample from well X in South Sumatra as an imbibition fluid. This stimulation uses the optimum nutrients concentration as fix variable and artificial core permeability as independent variable with exact values (± 5; 15; 50; 150; 300 mD). The tertiary oil recovery could be determined by oil that comes out to graduated tube during imbibition experiment. From the results of the stimulation, nutrients biostimulation will increase tertiary oil recovery as the increase in permeability which starts from ±50 mD. The highest value of tertiary oil recovery that can be seen from Incremental Recovery Factor (IRF) is 4.2% in core with permeability ±300 mD. Nutrients also can stimulate bacterial growth inside the core and the bacterial colonize the rock which can be seen from the result of increasing number of facultative anaerob bacterial cells from 1.32 x 105 to 2.55 x 106 CFU/ml and anaerob bacterial cells 8.14 x 104 CFU/ml to 6.95 x 105 CFU/ml after 14 days imbibition period.